Pelatihan Public Speaking dan Focus Group Discussion - Menuju Kepemimpinan yang Inspiratif dalam Berorganisasi di SMA Islam 1 Sleman - Nabila Putri Nawati; Putri Isnu Marthania; Moni Sulistiyawati; Yuliami Anggi Saputri; Anjessa Putra; M. Alfian Dwi Cahya; Popi Andiyansari (Universitas Teknologi Yogyakarta, 2025)
Public speaking training is a very important skill in the world of organizations, especially for students who are members of OSIS. The activity